Implementing Triple Bottom Line Accounting to Transform MSME Sustainability - Lubis, Nurliza; Harahap, Ainul Yusra; Faridy, Najihatul (INTERNATIONAL JOURNAL OF TRENDS IN ACCOUNTING RESEARCH, 2024)
This study examines the impact of the Triple Bottom Line (TBL) accounting concept on the financial performance of MSMEs in Langsa. Through quantitative analysis using regression and MANOVA, the research evaluates how TBL implementation affects net income, cost growth, and cost efficiency. Results show that TBL has a significant positive effect on net income with an R Square value of 46%, indicating that TBL explains nearly half of the variation in MSMEs' financial performance. While cost growth increases in the short term, consistent with the initial expenses of sustainable practices, TBL leads to cost efficiency improvements over time, with an R Square of 27.4%. MANOVA results confirm that TBL simultaneously affects all three financial variables significantly. The findings support the hypothesis that TBL implementation enhances both financial sustainability and long-term business success for MSMEs, balancing profitability, social responsibility, and environmental stewardship